2017
DOI: 10.1038/s41598-017-06136-9
|View full text |Cite
|
Sign up to set email alerts
|

Mass-spectrometry analysis of modifications at DNA termini induced by DNA polymerases

Abstract: Non-natural nucleotide substrates are widely used in the enzymatic synthesis of modified DNA. The terminal activity of polymerases in the presence of modified nucleotides is an important, but poorly characterized, aspect of enzymatic DNA synthesis. Here, we studied different types of polymerase activity at sequence ends using extendable and non-extendable synthetic models in the presence of the Cy5-dUTP analog Y. In primer extension reactions with selected exonuclease-deficient polymerases, nucleotide Y appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Intrigued by these results, we analyzed the products stemming from the PEX reactions conducted with the combination of Taq polymerase and 3′-phos-dTTP 5 as well as that with Therminator and 3′-phos-LNA-TTP 10 by LCMS (Table 1 , Supplementary Figs. 23 – 28 , and Supplementary Note 1 ) using established protocols for products stemming from PEX reactions with natural and modified nucleotides 51 , 52 . This analysis clearly revealed that 1. no phosphorylated nucleotide was incorporated by polymerases and that 2. dA nucleotides were misincorporated opposite templating dAs instead of the modified triphosphates.…”
Section: Resultsmentioning
confidence: 99%
“…Intrigued by these results, we analyzed the products stemming from the PEX reactions conducted with the combination of Taq polymerase and 3′-phos-dTTP 5 as well as that with Therminator and 3′-phos-LNA-TTP 10 by LCMS (Table 1 , Supplementary Figs. 23 – 28 , and Supplementary Note 1 ) using established protocols for products stemming from PEX reactions with natural and modified nucleotides 51 , 52 . This analysis clearly revealed that 1. no phosphorylated nucleotide was incorporated by polymerases and that 2. dA nucleotides were misincorporated opposite templating dAs instead of the modified triphosphates.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of thymidine phosphoramidite derivative 2 with activated carboxylic acid residue at the N3 position of the pyrimidine heterocycle is outlined in Scheme 1 . The synthesis of 5′-O-(4,4′-dimethoxytrityl)-N3-carboxymethylthymidine was carried out as described previously by selective N-alkylation of the partially protected thymidine with ethyl bromoacetate in the presence of DBU, followed by alkaline hydrolysis [ 6 , 17 ]. Further activation of the carboxyl group smoothly proceeded upon treatment with an excess of pNP-TFA ester in pyridine [ 18 ].…”
Section: Resultsmentioning
confidence: 99%